Empowerment of The Village Forest Management Institution Baharu through Optimizing the Utilization of Bamboo in Foramadiahi - Firlawanti Lestari Baguna; Fadila Tamnge; Andy Kurniawan; Ramli Hadun; Aqshan Shadikin Nurdin; Much Hidayah Marasabessy (Universitas Muhammadiyah Palembang, 2023)
The lack of public in using bamboo is due to the absence of a market and lack of public. Optimizing the use of bamboo can help society increase an economic household. The aim of carrying out service activities is to improve the skills and abilities of the village forest management institution or LPHD Baharu in using bamboo as a basic material for crafts and being able to understand the concept of an independent community economy. The activity was carried out at LPHD Baharu of Foramadiahi in Ternate, North Maluku. Activities were carried out with the LPHD forest farmers group in Foramadiahi. The method used is socialization and training to process bamboo into crafts that have marketable value. All stages of activities were carried out well and supported by community participation. Some of the uses of bamboo in Foramadiahi are as house fences, braces (gata-gata), and support poles (house building materials/concoctions). Apart from that, bamboo can also be processed into various crafts and weaves. It is hoped that these activities can provide knowledge and skills for the community to develop the potential of bamboo in Foramadiahi so that it can help the community become an independent sub-district.